Pengaruh Literasi Rumah terhadap Kemampuan Membaca Permulaan Anak Prasekolah - Kusumawardhani, Trully; Dhieni, Nurbiana; Yetti, Elindra (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Early reading and writing skills, or known as early literacy, is crucial for supporting successful reading and writing during school age. Early literacy is closely related to home literacy, as the two influence each other. However, early reading skills remains low in Indonesia. Therefore, the aim of this study is to determine how home literacy affects the early reading skills of preschool children., both with or without controlling for parental age, occupation, and education. The method used in this study is a quantitative descriptive method using a multiple regression model approach. The samples in this study consist of preschool children and their parents from Little Bee Moslem Kindergarten and Al Kayyisah Kindergarten. Sampling was determined using multistage random sampling. The results of this study show that, with or without controlling for parents' age, parents' occupation, and parents' education, home literacy affects preschool children's early reading skills. All effects were equally influential, except for the impact of constraints on reading with children and the parents' occupation.